EFFECT OF HEAT TREATMENT TEMPERATURE ON MICROSTRUCTURE CHARACTERISTIC AND HARDNESS PROPERTIES OF CASTED Ti-6Al-4V ELI - Damisih Damisih; I Nyoman Jujur; Joni Sah; Djoko Hadi Prajitno (Pusbindiklat - LIPI, 2018)
Ti-6Al-4V Extra Low Interstitial (ELI) alloys have been widely used for biomedical application as implant materials due to its excellent mechanical properties and good corrosion resistance. Furthermore, mechanical properties of this alloy could be improved by heat treatment process. In this research, it has been studied the effect of heat treatment temperature on microstructure and hardness properties of casted Ti-6Al-4V ELI alloy. After calculation of material balance to obtain this alloy composition, raw materials were melted using single arc melting furnace flowed with argon gas and melted alloy was casted. Then, it was heat treated by solution treatment for around 1 hour and subsequently quenched in water as medium. Solution temperature was given with temperature variables of 850oC, 950oC and 1050oC. After that, it was aged at temperature of 500oC for 4 hours. Microstructures were observed using optical microscope and hardness value were obtained by Vickers hardness method. The results of microstructure observation showed that it was changed after heat treatment process, especially on morphology of α and β phase. Thus, the hardness of alloy significantly increased compared with as-cast condition after heat treatment process. The optimum value of hardness was obtained at temperature of 850oC that was 478 HVN.